MAIN WAYS TO IMPROVE THE FINANCIAL CONDITION OF THE ENTERPRISE - Maysigova Leyla; Satymbekova Katira; Nurgaliyeva Аinash; Imanbayeva Zauresh Otegenkyzy; Kerimbek Galymzhan (Scientific Journal of Pedagogy and Economics, 2020)
The purpose of the analysis of the financial condition of the enterprise is to timely identify the shortcomings of the enterprise and their elimination, search for sources of improving the solvency of the enterprise. This determines the main tasks of analyzing and evaluating the financial condition of the enterprise. Principles of financial analysis is the continuity of the state and development of financial processes, consistency, significance, objectivity, reliability, resilience of these forms of financial reporting, practical relevance, comprehensiveness, unity and consistency, clarity of interpretation of the results of financial analysis, frequency and effectiveness of management decisions. A number of enterprises face a shortage of funds necessary to finance their economic activities, due to the restriction of their own resource base as a result of the transition of the financial situation to an inefficient value. In this case, enterprises should reduce or completely stop production activities. Accordingly, the decline in production increases in the country, the crisis level deepens, that is, there is a decrease in the resources used for payments between enterprises and the state, between enterprises themselves and other economic entities. As a result, there is a multiplicative effect: a break in one place in the calculation chains instantly moves along the line, increasing its strength and directly and indirectly affects other participants with other social name. An analysis of methods for assessing the financial position will lead to the conclusion that a single methodology for selecting financial position standards is not ready. Many economists and financiers in the analysis of the financial situation, along with various blocks, determine different indicators of financial stability and their normal values. The questions that arise when choosing methods for assessing financial conditions based on review and comparison of special foreign literature are brought in order.